Does Parental Presence Influence Child Performance on an Emotional Go/No‐Go Task at Age 9.5? Exploring the Role of Puberty and Early Environmental Quality - Nolvi, Saara; Perasto, Laura; Juntunen, Pauliina; Autere, Tuomo‐Artturi; Huovinen, Venla; Luotola, Aino; Audah, Hilyatushalihah Kholis; Karukivi, Max; Aatsinki, Anna‐Katariina; Karlsson, Hasse; Karlsson, Linnea; Lukkarinen, Minna; et al. (Wiley, 2026)
Previous research suggests that children may perform better and regulate emotions more effectively in the presence of a parent than an unfamiliar stranger, a phenomenon known as parental buffering. This reliance may vary with pubertal development and early psychosocial environments. However, existing studies often rely on small, mixed-age samples and provide limited insight into how normative variation in caregiving quality and parental mental health influences children's transition from parental dependence to independent regulation before puberty. In this pre-registered study, we examined children's performance on an emotional go/no-go task under parent-present versus stranger-present conditions in a large sample of 9.5-year-old children (N = 501) from the FinnBrain Birth Cohort Study. In smaller subsamples, we tested whether pubertal stage affected parental effects on performance and whether early maternal caregiving quality and long-term parental distress moderated these effects. We did not find consistent evidence for parental buffering of 9.5-year-olds’ performance in either pre-pubertal or pubertal children. However, sensitivity analyses including all trials, with effect sizes resembling those of the main models, suggested that children made fewer errors when a parent (vs. a stranger) was present, consistent with our pre-registered hypotheses. Evidence for moderation by early caregiving quality or parental mental health was minimal. These findings highlight the need for longitudinal, age-specific research on children's reliance on parental presence for emotion regulation and suggest that typical variation in caregiving quality and parental mental health may not substantially influence parental buffering effects in middle childhood.